Psychological well-being and gene expression in Korean adults: The role of age. (October 2020) - Lee, Sung-Ha; Choi, Incheol; Choi, Eunsoo; Lee, Minha; Kwon, Yuri; Oh, Bumjo; Cole, Steven W.
Highlights: Higher eudaimonia links to reduced inflammatory gene expression, CTRA. Psychological well-being (PWB) is associated with reduced CTRA in Korean adults. Among subscales of PWB, autonomy showed the strongest inverse correlation with CTRA. The inverse association between PWB and CTRA is stronger for older participants. Abstract: Background: Happiness has traditionally been thought to comprise two parts - pleasure (hedonia) and meaning (eudaimonia). Even though the two types of happiness are correlated, genomics studies have found distinct transcriptional correlates of hedonia and eudaimonia, particularly in the Conserved Transcriptional Response to Adversity (CTRA) marked by up-regulation of proinflammatory genes and down-regulation of interferon-related genes. Eudaimonia has been associated with reduced CTRA gene expression in several studies, whereas hedonia shows no consistent association with the CTRA. However, most of these social genomics studies have been conducted in Western cultures with Caucasian samples, so it is unclear if these findings extended to non-Western cultures with other ethnic groups. Moreover, it is unknown whether age might modify the association between CTRA gene expression and eudaimonia. To this end, we examined in a sample of Koreans the relationship between CTRA profiles and measures of hedonia and eudaimonia, as well as the role of age in modulating the strength of those relationships. Methods: Blood samples were collected from 152 healthy Korean adults (mean age = 44.64; 50 % female). Well-being was measured using the Mental Health Continuum short form (MHC-SF), Ryff Scales of Psychological Well-being (PWB), and subjective well-being (SWB) scales. RNA transcriptome profiles were obtained by RNA sequencing. Mixed effect linear model analyses examined the association between CTRA gene expression and measures of MHC-SF, SWB, PWB (total scores and six subscales) and additional analyses examined a possible moderating role of age. Results: CTRA gene expression was significantly downregulated in association with the MHC-SF eudaimonic scores as well as the PWB total scores. Among the six domains of PWB, autonomy showed the strongest inverse correlation with CTRA profiles. Moreover, the inverse association between CTRA and PWB was stronger for older participants. Conclusion: Eudaimonia is associated with reduced CTRA gene expression in a Korean population, with particularly marked relationships for autonomy. Findings also suggest that aging with meaning may bring biological advantage in later life.